DETERMINAN INDEKS HARGA SAHAM GABUNGAN DENGAN NILAI TUKAR SEBAGAI VARIABEL MODERASI - Riswanto, Gendy; Riyanto, Wahyu Hidayat (Journal of Financial Economics & Investment, 2025)
Indonesian Stock Exchange provides a forum for assessing the performance of all shares which can be seen or listed on Composite Stock Price Index. This research aims to determine and understand the influence of, Bank Indonesia interest rates, the money supply, and Bank Indonesia interest rates and the amount of money in circulation on the Composite Stock Price Index, using exchange rates as a moderating variable. By utilizing secondary data for the 2021-2023 period from www.ksei.co.id, www.satudata.kemendag.go.id, and www.idx.co.id, regression analysis was carried out using Smart PLS software. The results of analysis show that the BI rate and money supply have a significant influence on the composite stock price index. On the other hand, the exchange rate shows an inability to moderate or weaken the relationship between the BI rate and the amount of money in circulation on the Composite Stock Price Index. The implications of this research are to design effective policies in maintaining the stability of the capital market and exchange rates by the government and financial authorities as well as the basis for making investment decisions, especially anticipating the impact of exchange rate fluctuations on stock market movements.